Rwanda continues to develop a national policy framework for climate services under the UN Global Framework for Climate Services - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
Building on CCAFS innovation and engagement, the Rwanda National Meteorological Agency has convened two stakeholder workshops to initiate a National Framework for Climate Services (NFCS). The NFCS is a policy framework and multi-sector coordinating mechanism, under the UN Global Framework for Climate Services, to facilitate the development and delivery of climate services to manage risks across climate-sensitive sectors. The NFCS process contributes toward the SDGs, Rwanda's National Strategy for Transformation, and Rwanda's Green Growth and Climate Resilient Strategy.